MENGUJI FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KETAATAN PAJAK - Suwito, Edy (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2017)
This research has a purpose to test the effect of Tax Sanction, Tax Awareness, Tax Service, and Level of Tax Understanding on Tax Obedience, with research object of KPRI in Madiun city, the result of this research confirms that the factors above influence tax obedience